The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.vaccine.2018.09.068
|View full text |Cite
|
Sign up to set email alerts
|

An inactivated poliovirus vaccine using Sabin strains produced on the serum-free PER.C6® cell culture platform is immunogenic and safe in a non-human primate model

Abstract: BackgroundThe World Health Organization recommends the development of affordable next-generation inactivated poliovirus vaccines (IPV) using attenuated poliovirus Sabin strains. Previously, we introduced a novel PER.C6® cell culture platform, which allows for high yield production of an affordable trivalent Sabin IPV vaccine.MethodsImmunogenicity and safety of this novel PER.C6®-based Sabin-IPV (sIPV) was assessed in rats and non-human primates (NHPs). NHPs received one of four different dose dilutions vaccine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…23 The IPV evaluated here is based on the safer-tomanufacture Sabin poliovirus strains and the PER.C6® platform. This platform supports a high productivity of polioviruses, [27][28][29] which showed immunogenicity in preclinical models. 29 We describe here the first clinical assessment of the PER.C6® sIPV in adult volunteers.…”
Section: Introductionmentioning
confidence: 58%
“…23 The IPV evaluated here is based on the safer-tomanufacture Sabin poliovirus strains and the PER.C6® platform. This platform supports a high productivity of polioviruses, [27][28][29] which showed immunogenicity in preclinical models. 29 We describe here the first clinical assessment of the PER.C6® sIPV in adult volunteers.…”
Section: Introductionmentioning
confidence: 58%
“…Substitution of Sabin strains or the new candidate OPV strains for IPV strains in a new inactivated polio vaccine (sIPV) to provide safe, affordable next-generation inactivated poliovirus vaccines is another alternative that is currently being explored [80,82,248,251,[253][254][255]. Chumakov et al [82] suggested four possible solutions to the problem of lower stability and immunogenicity of Sabin OPV strains when inactivated to be used for IPV: (1) increase antigen content to a level that would ensure adequate seroconversion (disadvantages: it requires growing greater quantities of virus made more difficult since yields of Sabin strains are lower than wildtype viruses; increases costs); (2) stimulate immunogenicity with adjuvants; (3) explore use of alternative inactivating agents that do not damage antigens as much as formaldehyde; and (4) make IPV from new, genetically stable, nonpathogenic, hyperattenuated engineered poliovirus strains with antigenic structures identical to the currently used wild-type strains [34,256].…”
Section: Poliovirus Infections At the Level Of The Individual Hostmentioning
confidence: 99%
“…Differences in antigenic structure of inactivated polio vaccines made from Sabin live attenuated and wild-type poliovirus strains effected equivalency of vaccine potency assays used to measure the D-antigen content of the vaccines [255]. This required development of new international standard, IS 12/104, for sIPV [80,81].…”
Section: Future Directions: the Endgame Stage Of Eradication And Sustmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Optimization of the vaccine manufacturing process via the usage of less infectious virus strains became a priority to allow IPV production in middle- and low-income countries due to the unacceptable biosafety risks accompanied with conventional IPV production. IPV developed from live-attenuated Sabin strains (sIPV) was a reasonable alternative and many studies proved its efficacy and affordability [ 11 , 12 , 13 , 14 ]. In 2012, manufacturers in Japan and China were licensed for production and marketing of Sabin-IPV and this vaccine is used there extensively.…”
Section: Introductionmentioning
confidence: 99%